PENGARUH KECERDASAN SPIRITUAL DAN KOMITMEN ORGANISASIONALTERHADAPORGANIZATIONAL CITIZENSHIP BEHAVIORMELALUI KEPUASAN KERJA SEBAGAI VARIABEL INTERVENING - Baiq Ayu Ningsih; Surati Surati; Siti Nurmayanti (Master of Management, Mataram University, 2019)
This study examined the effect of spiritual intelligence and organizational commitment on job satisfaction and OCB on Non-PNS Leading Sector Assistant III East Lombok Regency employees. Specifically the purpose of this study was to determine the significance of the influence of spiritual intelligence, organizational commitment and job satisfaction on OCB, determine the significance of the influence of spiritual intelligence and organizational commitment on job satisfaction, and find out the mediating role of the variable job satisfaction. The population of this study were all Non-PNS employees who served in the Leading Sector Assistant III of East Lombok Regency as many as 98 respondents. This study uses structural equation model analysis (SEM analysis) with smartPLS applications. The results showed that spiritual intelligence and organizational commitment had a significant positive effect on job satisfaction, job satisfaction had a significant effect on OCB, while spiritual intelligence and organizational commitment did not significantly influence OCB. For the mediating effect of job satisfaction, there is a full mediation role in the significant influence of organizational commitment on OCB, whereas the influence of spiritual intelligence on OCB has not found a significant mediating effect of the variable job satisfaction.Keywords:Spiritual Intelligence, Organizational Commitment, Job Satisfaction, OCB.